Superior vena cava aneurysm: difficulty in preoperative diagnosis - Kądziołka, Wojciech; Kobak, Grzegorz; Kądziołka, Joanna; Kaznowska, Ewa; Guz, Wiesław; Rybka, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Superior vena cava aneurysms are extremely rare lesions. We describe a case of a 52-year-old woman. Chest roentgenogram suggested the presence of mediastinal mass in the right hemithorax and after the computed tomography test, we had the clinical impression that it was a mediastinal cyst not enhancing after intravenous contrast application. Thoracotomy revealed superior vena cava aneurysm which was successfully resected. We report this because of its extraordinary rarity. There are only a few cases like that described in the literature